Assessment of nonarteritic anterior ischemic optic neuropathy with intravoxel incoherent motion diffusion‐weighted imaging using readout‐segmented echo‐planar imaging, parallel imaging, and 2D navigator‐based reacquisition. Issue 6 (17th May 2017) - Lu, Ping; Sha, Yan; Wan, Hailin; Wang, Feng; Tian, Guohong; Tang, Wenlin
Abstract : Purpose: To determine the feasibility of intravoxel incoherent motion (IVIM) for characterizing perfusion properties and its potential diagnostic utility for nonarteritic anterior ischemic optic neuropathy (NAION). IVIM diffusion‐weighted imaging is a promising technique that can measure perfusion and diffusion characteristics simultaneously in a noninvasive manner. Materials and Methods: Orbital IVIM in a 3.0T scanner was performed on 33 patients with NAION and 15 controls using readout‐segmented echo‐planar imaging, parallel imaging, and 2D navigator‐based reacquisition (RESOLVE‐IVIM). Both visual field (VF) and visual acuity (VA) examinations were performed in 19 of the patients. The vascular volume fraction (f), diffusion coefficient (D), and pseudodiffusion coefficient (D*) were calculated for quantitative analysis. Additionally, correlation analyses of IVIM parameters with visual function were also performed. Results: Affected optic nerves showed significantly lower f values than both unaffected contralateral nerves of the patients and nerves of the controls ( P < 0.0001), and no significant difference for f was found between unaffected contralateral nerves and nerves of the controls ( P = 0.1602). In addition, D and D* values showed no significant differences among the three groups ( P = 0.0979, 0.0600, 0.6136 for D and 0.1779, 0.6253, 0.4743 for D*). Correlation analysis only demonstrated significant correlations between f values and the mean deviation of the visual field ( r = 0.576, P = 0.0051). Conclusion: RESOLVE‐IVIM measurement may reflect the perfusion abnormality and visual function impairment in NAION patients, demonstrating its potential application for the diagnosis and clinical evaluation of NAION. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2017;46:1760–1766.